Measurement of sigma(p(p)over-bar -> Z plus X)Br(Z -> tau(+)tau(-)) at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazovn, G.; Alton, A.; Alverson, G.; et al. (Elsevier B.V., 2009)
We present a measurement of the cross section for Z boson production times the branching fraction to tau lepton pairs sigma(p (p) over bar -> Z + X)Br(Z -> tau(+)tau(-)) in p (p) over bar collisions at root s = 1.96 TeV. The measurement is performed in the channel in which one tau lepton decays into a muon and neutrinos. and the other tau lepton decays hadronically or into an electron and neutrinos. The data sample corresponds to an integrated luminosity of 1.0 fb(-1) collected with the do detector at the Fermilab Tevatron Collider. The sample contains 1511 candidate events with an estimated 20% background from jets or muons misidentified as tau leptons. We obtain sigma . Br = 240 +/- 8 (star) +/- 12 (sys) +/- 15 (lum) pb, which is consistent with the standard model prediction. (C) 2008 Elsevier B.V. All rights reserved.